KOMUNIKASI INSTRUKSIONAL GURU DAN SISWA PADA PROGRAM KEWIRAUSAHAAN DI SEKOLAH LUAR BIASA BASO KABUPATEN AGAM - Ramadhani, Zahra Qabla; Susanti, Hevi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The entrepreneurship program is one part of the P5 subject (Pancasila Profile Strengthening Project) which is attended by mentally and deaf students at the SDLB, SMPLB and SMALB levels at SLB Baso. The purpose of this research is to determine the learning methods used, learning media and obstacles that occur during the entrepreneurship learning process in the classroom. This study used qualitative research methods. The subjects in this research were the principal, P5 coordinator, teachers and parents of SLB Baso students who were selected using a purposive technique. Data collection techniques consist of observation, interviews and documentation. Meanwhile, data analysis techniques consist of data reduction, data presentation and verification/drawing conclusions. The technique for checking the validity of the data used in this research is source triangulation, technique triangulation and time triangulation. The results of this research show that teachers' instructional methods in the entrepreneurship learning process are divided into lecture methods, sign language methods, demonstration methods, total communication, discussion/question and answer methods, and drill/exercise methods. Entrepreneurship learning media is in the form of visual and audio visual media. Barriers to instructional communication in the classroom learning process include barriers to teachers as communicators, such as teachers having difficulty communicating with students. Barriers to students as communicants are limited language and use of the vocabulary they have, making it difficult to understand the teacher's intentions. Barriers to media/channels, such as the lack of teaching aids and facilities that support entrepreneurial learning. Keywords: Instructional Communication, Entrepreneurship, Extraordinary School